A web-based E-learning and assessment portal - Wai Mon Theint (2018)
Virtual education is an emerging concept. Here the classes are not taken face-to-face in a classroom but through an electronic medium as a substitute. These virtual classrooms are gaining importance every day and very soon they are going to be an integral part of our world. Taking up these virtual classes through an electronic medium is termed as E-Learning. Today E- Learning is no more a technical word that only a few people know. It is turning to be a part of everyone's life whether a student, employee or a housewife all tend to use E-Learning in one way or another. Larger organizations are turning towards E-Learning solution for proving training digitally. As the number of Internet access points are growing rapidly, E-Learning is also gaining a new peak. This electronic medium serves best for dissemination of information. E-Learning is proving itself as a boon for students especially for the disabled who are not able to go and attend the lectures. All these emphases the need for developing an Open Source software that can be used to generate rich multimedia environment for E-Learning.